Plastic bottle feeding produces changes in biochemical parameters in human infants - A pilot study - Mahendra K. Pant; Abul. H. Ahmad; Manisha Naithani; Jayanti Pant (The Korean Pediatric Society, 2022)
Background Plastic bottles are widely used by people to feed their infants when breastfeeding is not possible. Bisphenol A (BPA), an endocrine disruptor is widely used in the manufacturing of plastic wares and is leached out from these plastic wares on exposure to high temperature, changed pH, or cleaning the plastic wares by harsh detergents. Purpose Feeding through plastic bottles over prolong duration is expected to expose the infants to leached BPA. Hence the present study was taken up to compare the effects of breastfeeding and plastic bottle feeding on biochemical parameters in infants and also detect for the presence of free BPA or its metabolite in the infants. Methods Biochemical tests like lipid profile, liver function tests, creatine-kinase-MB (CK-MB), serum urea, serum electrolytes were performed on blood samples obtained from infants who were breastfed and plastic bottle fed. Further, plasma and urine samples of the infants were subjected to Liquid chromatography-mass spectrometry analysis for detecting free BPA and BPA glucuronide. Results Biochemical changes in form of raised triglycerides, cholesterol, low-density lipoproteins, very low-density lipoproteins and increase in CK-MB, serum urea were observed in plastic bottle fed infants. BPA glucuronide was also detected in the urine of these infants. Free BPA was not detected in plasma or urine samples of the infants except in one plasma sample from bottle-fed group. Conclusion Plastic bottle feeding may lead to toxic changes in the functioning of organs which manifest as altered biochemical parameters.